Perfil nutricional e bioquímico de indivíduos em abstinência de crack e cocaína - Oliveira, Isabella Varanda (2017)
Drug use is a global problem disseminated among men and women, regardless of age and social class, and may affect the nutritional status of its users. The objective was to evaluate the biochemical, anthropometric, dietary and body composition of chemical dependents in the phase of abstinence, according to sex. In this study, 30 crack/cocaine users in withdrawal were recruited: 14 men and 16 women, all of them in treatment at the Sao Francisco de Assis Farm in Alegre-ES and the Casa da Paz Rehabilitation Clinic in Cachoeiro de Itapemirim – ES. After general anamnesis and blood pressure measurement the following parameters were evaluated: lipid profile, complete blood count, blood glucose, insulin, C-reactive protein, alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase, and gammaglutamyltransferase. It was also measured body weight, height, waist circumference, hip circumference, triceps skinfold thickness, biceps skinfold thickness, subscapular skinfold thickness, suprailiac skinfold thickness, waist-hip ratio, waistheight ratio, and body mass index. Body composition evaluation was performed by tetrapolar bioimpedance. Food intake was evaluated prior and during the abstinence period; first by the Food Frequency Questionnaire, and last by the 24 hour recall and by the revised diet quality index. Food intake was quantified in daily per capita. For the comparison between the gender, the Shapiro-Wilk Normality Test was applied, followed by the Student t test or Mann-Whitney test, for parametric or non-parametric data, respectively. For the correlations, the Pearson or Spearman test was applied, depending on the characteristics of the variables, parametric or non-parametric, respectively. It was found high levels of total cholesterol (53.33%), triacylglycerols (36.67%), LDL (46.67%), VLDL (33.33%), Castelli I index (40%) and Casteli II index (36.67%); as well as low HDL levels (76.67%). Also, it was observed high prevalence of overweight (72.33%), excess body fat (76.67%); as well as high waist circumference (63.33%), waist-hip ratio (40%) and waist-height ratio (70%). In relation to the food frequency questionnaire, it was observed frequent consumption of foods rich in carbohydrates and proteins, and low consumption of fruits and vegetables. According to the 24 hour recall, there was excess consumption of total cholesterol (36.67%), saturated fatty acids (46.67%), free sugar (96.67%); and low intake of calcium (60%), iron (30%), zinc (23.33), magnesium (60%), retinol (96.67%), vitamin D (96.67%), vitamin C (43.33%), vitamin E (100%), and fibers (80%). The revised diet quality index demonstrated that the individuals' diet needs modifications. There was a positive correlation of triacylglycerols and VLDL between the waist circumference, waist-height ratio, waist-hip ratio, muscle mass, and diastolic blood pressure. Furthermore, positive correlations were observed between the beginning of crack and cocaine use and the levels of ALT, GGT, triacylglycerols, VLDL, Castelli I index and Castelli II index. The majority of users of crack and cocaine studied presented risks of chronic diseases, particularly cardiovascular problems, due to the high consumption of total cholesterol, saturated fatty acids and free sugar, low micronutrient consumption, as well as the excess of weight and body fat and elevated blood lipid levels. Some showed a risk of liver damage due to changes in ASL, ALT, GGT, CRP and alkaline phosphatase levels.